Critical factors influencing user experience on passive exoskeleton application: A review - Halim, Isa; Zainal Abidin, Muhammad Zaimi; Abdullah, Shariman; Abdullah, Zulkeflee; A. Perumal, Puvanasvaran; Muhammad, Mohd Nazrin; Saptari, Adi (Penerbit UTHM, 2022)
Wearable assistive devices such as passive exoskeleton have been recognized as one of the effective solutions to assist people in industrial work, rehabilitation, elderly care, military and sports. The design and development of a passive exoskeleton that emphasizes on satisfying and fulfilling users’ requirements and users’ experience are essential to ensure the device remains competitive in the global market. A good user experience of using an exoskeleton stimulates users’ satisfaction, as contemporary users are not only considering basic functional features but also fascinated by perception values such as aesthetics and enjoyment. The main purpose of this article is to review the critical factors that are influencing user experience before, during and after utilizing a passive exoskeleton. The authors had searched relevant articles from academic databases such as Google Scholar, Scopus and Web of Science as well as free Google search for the publication period from 2001 to 2021. Several search keywords were used such as ‘passive exoskeleton + user experience’, ‘passive exoskeleton + industry’, ‘passive exoskeleton + rehabilitation’, ‘passive exoskeleton + military’, ‘passive exoskeleton + sports’, ‘passive exoskeleton + sit-stand’, and passive exoskeleton + walking’. This online search found that a total of 236 articles related to the application of passive exoskeleton in the area of industry, rehabilitation, military and sports. Out of this, 81 articles were identified as significant references and examined thoroughly to prepare the essence of this paper. Based on these articles, the authors revealed that the engineering design, usability, flexibility, safety and ergonomics, aesthetics, accessibility, purchase cost, after-sales service and sustainability are the critical factors that are influencing user experience when employing passive exoskeleton.